2006
DOI: 10.1111/j.1540-4609.2006.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining Drivers of Course Performance: An Exploratory Examination of an Introductory CIS Applications Course

Abstract: The accelerating diffusion of broadband Internet access provides many opportunities for the development of pedagogically robust Web-based instruction (WBI). While the supporting technology infrastructure of broadband disseminates, the attention of academic researchers focuses upon issues such as the drivers of student usage of WBI. Specifically, the research presented herein examined the impact of WBI on a student's aggregate course performance. We hypothesized that learning independence (LI) is a determinate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Another way to look at student success is through final course grades. Thus, in another model, I use the final course grade (out of 100) as the dependent variable (Baugher Varanelli Weisbord and Andrew 2003;Syler et al 2006). Because of the near-continuous nature of this dependent variable, ordinary least squares (OLS) regression models are used.…”
Section: Methodsmentioning
confidence: 99%
“…Another way to look at student success is through final course grades. Thus, in another model, I use the final course grade (out of 100) as the dependent variable (Baugher Varanelli Weisbord and Andrew 2003;Syler et al 2006). Because of the near-continuous nature of this dependent variable, ordinary least squares (OLS) regression models are used.…”
Section: Methodsmentioning
confidence: 99%
“…Student performance in online versus campus-based courses has been the subject of an increasing number of studies. The relevant literature has employed a student's grade as an indicator of course performance (Brecht & Ogilby, 2008;Buche, Davis, & Vician, 2007;Caspi & Gorsky, 2006;Chyung, 2007;Hiltz & Wellman, 1997;Irani, Telg, Scherler, & Harrington, 2003;Kock, Verville, & Garza, 2007;Loomis, 2000;Manochehri, & Young, 2006;McLaren, 2004;Newlin, Lavooy, & Wang, 2005;Puzziferro, 2008;Rabe-Hemp , Woollen, & Humiston, 2009;Syler, Cegielski, Oswald, & Rainer, 2006). Interestingly, among the studies comparing final course grade differences between online and campus-based students, many have not found the difference to be statistically significant (Benson, Johnson, Taylor, Treat, Shinkareva, & Duncan, 2005;Hiltz & Wellman, 1997;Kock et al, 2007;Manochehri, & Young, 2006;McLaren, 2004;Newlin, et al, 2005;Rabe-Hemp et al, 2009).…”
Section: Course Performancementioning
confidence: 99%
“…Loomis (2000) found that students reporting strong time management skills earned higher grades, suggesting their ability to better direct their studies pursuant with their own schedules. The use of web-based tutorials may indicate that students can achieve higher course grades (Syler et al, 2006). Comparing in-class and online sections, two separate studies found no statistically significant differences between students' final grades (Kock et al, 2007;Newlin et al, 2005).…”
Section: Course Performancementioning
confidence: 99%
See 1 more Smart Citation
“…However, recent research suggests that the style by which one learns and applies knowledge is an important characteristic to consider in the aggregate educational processes (Graf, Lin, & Kinshuk, 2008;Kolb & Kolb, 2009;Syler et al, 2006;Thorton, Haskell & Libby, 2006;Zualkernan, Allert, & Qadah, 2006). Acknowledgement of unique learning styles is an attempt to characterize the complex processes by which one acquires knowledge (Kolb, Rubin, & McIntyre, 1974).…”
Section: Introductionmentioning
confidence: 99%